2013
DOI: 10.3315/jdcr.2013.1156
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of skin diseases in a dermatology outpatient clinic in Turkey. A cross-sectional, retrospective study.

Abstract: It appears that certain skin diseases acne, fungal infections, contact dermatitis and urticarial cause serious health problems. Public health policies should be implemented in order to manage these problems rationally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
34
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 16 publications
(30 reference statements)
14
34
0
3
Order By: Relevance
“…These studies show an incidence rate of ≤3.8% [1,3,4,5,8] [13], and 4.48 in Erbil for the year 2012 [9]. In addition, this study incidence rate is highhigher to that reported for Palestine (17/100 000) for the years 2005-2010 [17] and Turkey (1.5%) for the year 2011 [18].…”
Section: Discussionsupporting
confidence: 45%
“…These studies show an incidence rate of ≤3.8% [1,3,4,5,8] [13], and 4.48 in Erbil for the year 2012 [9]. In addition, this study incidence rate is highhigher to that reported for Palestine (17/100 000) for the years 2005-2010 [17] and Turkey (1.5%) for the year 2011 [18].…”
Section: Discussionsupporting
confidence: 45%
“…Patients with alopecia areata represent a significant number of patients in dermatology hospitals and out‐patient clinics . The diagnostic options in alopecia areata have significantly increased in recent years .…”
Section: Resultsmentioning
confidence: 99%
“…This disease presents as erythematous patches with yellow and sometimes greasy scales. SD affects 1-3% of immunocompetent adults and recent studies revealed a similar prevalence (2.1-2.2%) of SD in male patients and those patients who visited the dermatology outpatient clinic [2][3][4]. The pathogenesis of SD is yet to be fully investigated but it has negative influences on the quality of life of patients suffering from SD [5,6].…”
mentioning
confidence: 99%